ANALISIS BERPIKIR KRITIS MATEMATIKA SISWA PADA MATERI PROGRAM LINIER DITINJAU DARI KEMAMPUAN AWAL MATEMATIKA DAN JENIS KELAMIN SISWA DI MA.ASSHOLACH KEJERON GONDANG WETAN PASURUAN - Bahiyah, KHORIDATUL BAHIYAH (Center of Education Journal (CEJou), 2023)
This stludy aims to analyze students' mathematical critlical thinking sklills on linelar programming material in terms of initial mathematical abillities and students' gender. This type of research is qualitative with a descriptive approach. The subjects in this study used class XI MA Asshlolach students consisting of 1 male student wilth high initial ability, 1 female student with high initial ability, 1 male student with low initial ability and 1 femlale student with low initial ability. Data collection techniques in this study are test techniques to measure critical thinking skills and non-test techniques in the form of interviews. The results of tests and interviews were analyzed based on indicators of critical thinking skills, namely: interpretation, analysis, evaluation and inference. The results showed that: (1) female students and male students with high and moderate initial abilities, it can be said that they have been able to carry out the stages of interpretation, analysis, evalluation, inference and explanation as well as self-regulation in solving critical thinking test questions. (2) female and male students with low initial abilities can already be said to be able to master 2 indicators of critical thinking skills (interpretation and evaluation), less able to master the indicators of analysis and inference.